فيزياء المقطع ونظرية الحركة والسكون - بين أصالة الدرس الصوتي عند العرب وحداثته عند الغرب - جديوي, روضة (University of Eloued جامعة الوادي, 2024)
ملخص: يندرج هذا العمل في إطار النَّشاط التَّأصيلي للدرس الصوتي العربي القديم في ضوء النّظريات الصّوتية الحديثة تنظيرًا وتطبيقًا، فهمًا وممارسةً. إِذَّاكَ تصبو رؤيتنا إلى التوقّف عند أهم المحطّات التي تأجّجت فيها النظرية الصوتية عند العرب، من خلال عرض مفهوم فيزياء المقطع ونظرية الحركة والسكون، ومقارنتهما بما توصّل إليه علم الأصوات الحديث. وقد قادنا التنقيب في هذا الموضوع إلى إماطة اللثام عن درس صواتي أصيل مكتمل ضارب بجذوره في عمق التراث العربي، مُتَمثّل للحداثة وما يبـرّرها من ديناميّة وتطور في الوسائل والإجراءات. الكلمات المفتاحية: فيزياء المقطع؛ الحركة والسكون؛ دينامية (حِراكية )التلفّظ؛ الجِرْس؛ الصِّرْف. Abstract: This research falls within the framework of the original activity of the ancient Arabic phonetic lesson in the light of modern phonetic theories theorizing and applying, understanding and practice. We aim to stop at the most important stations in which the phonetic theory developed among the Arabs, by presenting the concept of syllable physics and the theory of motion and stillness, and comparing them with what modern phonology has reached. Research on this subject has led us to discover an authentic and complete audio lesson that is deeply rooted in the Arab heritage, represented by modernity and its justified dynamism and evolution of means and procedures key words: Physics of the syllable; movement and stillness; dynamism of pronunciation; aljirss; assirf.
مقال. مجلة علوم اللغة العربية وآدابها. مج16 . ع.01. جامعة الوادي